Spectrophotometric analysis of Azithromycin and its pharmaceutical dosage forms: Comparison between Spectrophotometry and HPLC - Sharmin, Nahid; Shanta, Nazia Sultana; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2015)
A simple, reliable, precise and sensitive UV-spectrophotometric method was developed and validated for the estimation of azithromycin in pharmaceutical dosage form and compared with official USP 2010 method. The proposed method utilizes the oxidation of azithromycin with potassium permanganate to liberate formaldehyde. This formaldehyde reacts with acetone-ammonium reagent and produces yellow colored chromogen 3,5-diacetyl-2,6-dihydrolutidine. The colored solution exhibited a maximum absorption at 412 nm which can be detected with UVspectrophotometer. The method was found linear over the concentration range 80% to 120% of the working concentration (R2=0.999). The intra- and inter-day RSD (n = 6) was ? 2.0%. The developed method was validated according to ICH guidelines and values of accuracy, precision and other statistical analysis were found to be in good accordance with the prescribed values. The proposed method was successfully applied for determination of azithromycin and the results have been compared with HPLC and thus enabling the utility of this new method for routine analysis azithromycin in pharmaceutical dosage forms DOI: http://dx.doi.org/10.3329/dujps.v12i2.21981 Dhaka Univ. J. Pharm. Sci. 12(2): 171-179, 2013 (December)